2022
DOI: 10.3389/fnins.2022.921873
|View full text |Cite
|
Sign up to set email alerts
|

Functional changes in the auditory cortex and associated regions caused by different acoustic stimuli in patients with presbycusis and tinnitus

Abstract: Presbycusis and tinnitus are the two most common hearing related pathologies. Although both of these conditions presumably originate in the inner ear, there are several reports concerning their central components. Interestingly, the onset of presbycusis coincides with the highest occurrence of tinnitus. The aim of this study was to identify age, hearing loss, and tinnitus related functional changes, within the auditory system and its associated structures. Seventy-eight participants were selected for the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 75 publications
1
4
0
Order By: Relevance
“…Recent findings complement our previous reports about the functional (Fuksa et al, 2022 ) and gray matter (Profant et al, 2020 ) changes within the auditory and limbic systems induced by aging, hearing loss and tinnitus. Our study confirmed higher specificity of the FBA over DTI as regards to white matter changes within the auditory pathway above the IC, in comparison with our older report (Profant et al, 2014 ).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Recent findings complement our previous reports about the functional (Fuksa et al, 2022 ) and gray matter (Profant et al, 2020 ) changes within the auditory and limbic systems induced by aging, hearing loss and tinnitus. Our study confirmed higher specificity of the FBA over DTI as regards to white matter changes within the auditory pathway above the IC, in comparison with our older report (Profant et al, 2014 ).…”
Section: Discussionsupporting
confidence: 90%
“…From a functional standpoint, all three parameters; aging, hearing loss and tinnitus induce changes in the AC, and to a smaller degree also in the parts of the limbic system (Ins and HP; Fuksa et al, 2022 ). The functional engagement of limbic structures within the tinnitus network is further affirmed by the discoveries of De Ridder et al ( 2011 ) and Maudoux et al ( 2012 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A mixed group of older adults with mild and expressed presbycusis with and without tinnitus showed stronger activity in the left AC and less lateralization of activity compared to younger adults with a combined analysis of different acoustic stimulation (words, words in babble, modulated pink noise and babble) (Fuksa et al, 2022 ). However, it is not clear how much this result was affected by tinnitus and presbycusis.…”
Section: Functional Alterations—fmri Studiesmentioning
confidence: 99%
“…Therefore, ACh signaling should be considered an important modulator of excitatory neuronal function in the normal, as well as in pathological auditory pathways ( Roberts et al, 2013 ). For example, tinnitus-related increases in excitability at multiple subcortical and cortical structures may reflect pathological changes in nAChR function ( Norena, 2011 ; Auerbach et al, 2014 ; Ghimire et al, 2020 ; Fuksa et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%